Doubly transitive sets of even permutations - Nagy Gábor Péter (BULETINUL ACADEMIEI DE STIINTE A REPUBLICII MOLDOVA - MATEMATICA, 2016)
In this paper we investigate doubly transitive sets of permutations which consist of even permutations. © Gábor P. Nagy, 2016.